Effect of torso rotational strength on angular hip, angular shoulder, and linear bat velocities of high school baseball players - Szymanski, D. J.; McIntyre, J. S.; Szymanski, J. M.; Bradford, T. J.; Schade, R. L.; Madsen, N. H.; Pascoe, D. D. (The Journal of Strength and Conditioning Research, 2007)
This investigation examined the effect of torso rotational strength on angular hip (AHV), angular shoulder (ASV), linear bat-end (BEV), and hand velocities (HV) and 3 repetition maximum (RM) torso rotational and sequential hip-torso-arm rotational strength (medicine ball hitter's throw) in high school baseball players (age 15.4 +/- 1.2 y). Participants were randomly assigned to 1 of 2 training groups. Group 1 (n = 24) and group 2 (n = 25) both performed a stepwise periodized resistance exercise program and took 100 swings a day, 3 days a week, for 12 weeks with their normal game bat. Group 2 performed additional rotational and full-body medicine ball exercises 3 days a week for 12 weeks. A 3RM parallel squat and bench press were measured at 0 and after 4, 8, and 12 weeks. Participants were pre- and posttested for 3RM dominant and nondominant torso rotational strength and medicine ball hitter's throw. Angular hip velocities, ASV, BEV, and HV were recorded pre- and posttraining by a motion capture system that identified and digitally processed reflective markers attached to each participant's bat and body. Groups 1 and 2 increased (p = 0.05) BEV (3.6 and 6.4%), HV (2.6 and 3.6%), 3RM dominant (10.5 and 17.1%) and nondominant (10.2 and 18.3%) torso rotational strength, and medicine ball hitter's throw (3.0 and 10.6%) after 12 weeks. Group 2 increased AHV (6.8%) and ASV (8.8%). Group 2 showed greater improvements in BEV, AHV, ASV, 3RM dominant and nondominant torso rotational strength, and medicine ball hitter's throw than group 1. Groups 1 and 2 increased predicted 1RM parallel squat (29.7 and 26.7%) and bench press (17.2 and 16.7%) strength after 12 weeks. These data indicate that performing additional rotational medicine ball exercises 2 days a week for 12 weeks statistically improves baseball performance variables.